2016
DOI: 10.3390/batteries2010001
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study of Na2Fe1−xMnxP2O7 (x = 0, 0.25, 0.5, 0.75, 1) as Cathode Material for Rechargeable Na-Ion Batteries

Abstract: Sodium-ion batteries (SIBs) are considered a good choice for post-lithium devices. Transition metal sodium pyrophosphates are among the most interesting cathode materials for SIBs. Here we study the electrochemical properties of the system Na 2 Fe 1´x Mn x P 2 O 7 (x = 0, 0.25, 0.5, 0.75, 1). By means of cyclic voltammetry (CV) and galvanostatic experiments, we confirm that pure Fe and Fe-rich compounds are promising for application in sodium batteries, whereas Mn-rich samples are less satisfactory, at least i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Barpanda et al reported electrochemical properties of ␤-Na 2 MnP 2 O 7 which is same as the structure of Na 2 FeP 2 O 7 , as 3.6 V (Mn 2+ /Mn 3+ vs sodium anode) for 80 mAh/g [22]. The other groups also reported electrochemical properties in ␤-Na 2 MnP 2 O 7 [24][25][26][27][28] . On the other hand, some literatures are suggesting that ␤-Na 2 MnP 2 O 7 is electrochemically inactive rather than Na 2 FeP 2 O 7 [24,26] [22] Triclinic (P1) Three dimensional Octahedra 3.6 80 Na2CoP2O7 [4] Orthorhombic (Pna21) Layered Melilite tetrahedra 3.0 80 ing reagent.…”
Section: Introductionmentioning
confidence: 82%
“…Barpanda et al reported electrochemical properties of ␤-Na 2 MnP 2 O 7 which is same as the structure of Na 2 FeP 2 O 7 , as 3.6 V (Mn 2+ /Mn 3+ vs sodium anode) for 80 mAh/g [22]. The other groups also reported electrochemical properties in ␤-Na 2 MnP 2 O 7 [24][25][26][27][28] . On the other hand, some literatures are suggesting that ␤-Na 2 MnP 2 O 7 is electrochemically inactive rather than Na 2 FeP 2 O 7 [24,26] [22] Triclinic (P1) Three dimensional Octahedra 3.6 80 Na2CoP2O7 [4] Orthorhombic (Pna21) Layered Melilite tetrahedra 3.0 80 ing reagent.…”
Section: Introductionmentioning
confidence: 82%
“…This 3D open network presents 1D channels along different directions ([100], [−100], and [01–1]), where the Na ions are allocated and where they can diffuse, as reported in Figure g,h. This phase was observed for the systems containing Co, Fe, and Mn. ,,, All the described structures present 1D, 2D, or 3D pathways for the diffusion of Na ions, so making the whole class of compounds highly favorable for application in batteries.…”
Section: Introductionmentioning
confidence: 88%
“…The powder samples of the series of mixed-metal compounds Na 2 MP 2 O 7 were prepared by the traditional solid-state route , starting from stoichiometric amounts of Fe­(C 2 O 4 )*2H 2 O (Aldrich, 99%), Co­(C 2 O 4 )*2H 2 O (Aldrich, 99%), ZnO (Aldrich, >99%), NaH 2 PO 4 (Aldrich, 98%). The reagents were accurately mixed in acetone and the obtained mixture was then heated at 300 °C for 2 h to eliminate the organic components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of energy storage and the development of highperformance rechargeable alkali-ion batteries currently progress by the synthesis of new materials in the solid state by chemists and by combined experimental and theoretical studies of cation conduction in the crystal frameworks. In this context, diphosphates with the formula A 2 MP 2 O 7 (A + is an alkaline cation and M 2+ is a divalent cation) are a class of materials with interesting structural features and promising electrochemical performances (Erragh et al, 1991(Erragh et al, , 1998Sanz et al, 1999;Dridi et al, 2001;Shakoor et al, 2015;Tealdi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%